The Infuleence Of The Head Of The Village Office On The Effectiveness Of Employee Perfirmance At Ardipura Village Office,South JayaPura District,Jayapura City - Gobai, Frediel (Jurnal Sosial, Sains, Terapan dan Riset (Sosateris), 2025)
This study is entitled "The Influence of the Head of the Village Office on the Effectiveness of Employee Performance at the Ardipura Village Office, South Jayapura District, Jayapura City." The background of this research is based on the importance of the head of the village office's role as a leader in organizing, directing, and motivating employees to work effectively to achieve organizational goals. Employee performance effectiveness is greatly influenced by leadership, communication, and managerial styles applied by the head of the village office. Therefore, this study aims to determine the extent of the influence of the village head on the effectiveness of employee performance. The research uses a quantitative approach with descriptive methods and simple linear regression analysis techniques. The population of this study consists of all employees at the Ardipura Village Office, numbering 20 people, all taken as samples (saturated sampling). Data was collected through questionnaires, interviews, and documentation. The analysis results show that the village head significantly influences employee performance effectiveness. Based on regression test results, a significance value of 0.003 (p < 0.05) was obtained, indicating a positive relationship between the role of the village head and employee performance. This proves that the better the leadership applied by the village head, the higher the effectiveness of employee work. The conclusion of this study is that the village head plays an important role in influencing the effectiveness of employee performance. Therefore, it is recommended that the village head continuously develop leadership skills, communication, and human resource empowerment to create a productive and conducive working environment.